Individual And Institutional Professional Leadership in Vocational Education and Training: Motives, Beliefs and Styles (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2022)
Vocational education and training (VET in Australia, PVET in Europe), as a unified endeavour, has to balance the comparative wealth of the peak universities with the needs of the community and young people for the employabilty that VET can provide. VET needs to promote its scope and strengths collectively and individually, and we analyse some of them. The subtext is that the paper highlights the features of leading institutions on which institutions can model their future development. There is no one unewuivocal model of course, so this paper senitises leaders to salient issues.